Plasma homocysteine and blood pressure in small for gestational age children - Irene Melinda Louis; Adrian Umboh (Indonesian Pediatric Society Publishing House, 2013)
Background Homocysteine is associated with endothelial damage and hypertension. Increased plasma homocysteine levels are often accompanied by cardiovascular impairment, including hypertension. Small for gestational age children have been found to have morbidity and mortality in cardiovascular diseases. Objective To assess for a possible association between homocysteine level and blood pressure in small for gestational age children. Methods This observational study was undertaken from December 2011 to April 2012 in Prof. Dr. R. D. Kandou Hospital, Manado, North Sulawesi, on children who were born small for gestational age in year 2004-2005. Data was analyzed by T-test to compare homocysteine levels in small for gestational age and normal birth weight children. Regression analysis and simple coefficient test were used to assess for an association between homocysteine levels and blood pressure in children who were small for gestational age at birth. Results The mean homocysteine level in small for gestational age children was significantly higher than that of normal birth weight children (P<0.001). We observed no correlation between homocysteine level and systolic blood pressure in the small for gestational age group (r=0.151, P=0.189). However, there was a weak correlation between homocysteine level and diastolic blood pressure in the small for gestational age group (r=0.237, P=0.049). Conclusion Children who were small for gestational age at birth have significantly higher mean homocysteine level than that of normal birth weight children. Higher homocysteine levels are associated with higher diastolic blood pressure in children who were small for gestational age at birth.